Qualifying signs of the sentence: categorical and functional aspect (interpretation model of Alexandr Melnychuk) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The main parameters of sentence qualification by Alexander Melnychuk have been viewed, formal-structural, categorical-semantic and functional-tier aspects of scientist`s sentence interpretation have been characterized, and their specific features have been differentiated. Regularities of sentence realization in discourse have been identified. Signs of situation-pragmatic sentence marking in conversational speech and its correlativity with the expression have been diagnosed. The development of Alexander Melnychuk`s doctrine of sentences in modern linguistics has been observed.
Keywords: sentence; formal-structural aspect; categorical-semantic aspect; functional-tier aspect; expression